1998
DOI: 10.1073/pnas.95.5.2509
|View full text |Cite
|
Sign up to set email alerts
|

A simplified system for generating recombinant adenoviruses

Abstract: Recombinant adenoviruses provide a versatile system for gene expression studies and therapeutic applications. We report herein a strategy that simplifies the generation and production of such viruses. A recombinant adenoviral plasmid is generated with a minimum of enzymatic manipulations, using homologous recombination in bacteria rather than in eukaryotic cells. After transfections of such plasmids into a mammalian packaging cell line, viral production is conveniently followed with the aid of green fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2,873
0
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,224 publications
(2,886 citation statements)
references
References 26 publications
3
2,873
0
10
Order By: Relevance
“…Modified sequences were incorporated into the Ad genome by homologous recombination. 42,43 The left and right ITRs, E2F-1 promoter, SV40 pA, the E1A adenoviral gene, hTERT promoter, a portion of the adenoviral E3 region (bp 29,994-30,575) and c of the viral genome were sequenced by automated cycle sequencing using dye terminators and were found to be as predicted.…”
Section: Plasmids and Virusesmentioning
confidence: 92%
“…Modified sequences were incorporated into the Ad genome by homologous recombination. 42,43 The left and right ITRs, E2F-1 promoter, SV40 pA, the E1A adenoviral gene, hTERT promoter, a portion of the adenoviral E3 region (bp 29,994-30,575) and c of the viral genome were sequenced by automated cycle sequencing using dye terminators and were found to be as predicted.…”
Section: Plasmids and Virusesmentioning
confidence: 92%
“…The recombinant adenoviral vectors were generated by homologous recombination between a shuttle vector (pTrack-CMV) and the adenoviral backbone vector (pAdEASY-1). 31 The deletion of the adenoviral E1 renders the virus unable to produce infectious viral particles in target cells, and deletion of the E3 region is dispensable for viral production since it encodes proteins involved in evading host immunity. Both these deletions ensure the safety of this method of delivery.…”
Section: Adenoviral Infectionsmentioning
confidence: 99%
“…In some previous studies,29 GATA2 was reported as a transcription factor that inhibited PPARγ transcription by binding to its promoter. We found that NR4A1 was able to enhance the transactivation of GATA2 promoter (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Adenovirus encoding NR4A1‐haemagglutinin (HA) (Ad‐NR4A1‐HA) or Control adenovirus (Ad‐GFP) were amplified, purified and enriched according to standard technology 29. 3T3‐L1 cell was infected with NR4A1‐HA adenovirus (AD‐NR4A1) or control adenovirus (AD‐GFP) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%